The reproductive strategy of Leporinus friderici (Characiformes, Anostomidae) in the Paraná River basin: the effect of reservoirs - LOPES,C. de A. (2000)
The reproductive strategy of a species depends upon the interaction between intrinsic and extrinsic factors. Examining the population of Leporinus friderici in two reservoirs of the Upper Paraná River basin in reference to first gonadal maturation and breeding season and sites, the present investigation tested whether the environment formed by damming promoted spatial and temporal changes in the reproductive strategy of this species. Analyses of sex ratios showed that females significantly predominated in Itaipu, while in Corumbá the sexes were about equal with a slight predominance of males. Size-associated sexual dimorphism was observed, that is females dominated the longer length categories, and males the shorter. The minimum size at which L. friderici initiated reproduction varied from year to year, and was larger in the periods soon after formation of both reservoirs. In Itaipu, stabilization between the maximum and minimum lengths at first maturation was also noted after year 6 following closure and continuing until year 15. In general, the breeding season lasted from October through April, although cyclic changes in the duration and intensity of this season were evident. Young individuals predominated during the entire study period in Corumbá. The formation of Itaipu Reservoir had a greater effect on the reproduction of L. friderici, where a gradual adaptation of the reproductive strategy of this species may possibly have been occurring. It is also possible that some of the characteristics of the Itaipu population will in the future be shown by the Corumbá population. It was concluded that reproductive strategies constitute ecological adaptations that are temporally and spatially altered and are fitted to resource availability and environmental pressure.